Autonomia e participação na elaboração do Projeto Pedagógico online da SME de Campinas-SP - Carvalho, Rachel Teixeira de (2022)
This dissertation was carried out within the scope of the Study and Research Group on School Organization: Democracy, Human Rights and School Administrators’ Development – DEFORGES, and aimed to analyze whether the guiding documents for the construction of the online Pedagogical Project of the Municipal Department of Education of Campinas-SP can contribute to the improvement of democratic management in schools within the municipal education network. The central question was the following: how does the Municipal Education Department conceive the autonomy granted by the Law of Directives and Bases of National Education (BRAZIL, 1996) and lead the construction of the online Pedagogical Project? The specific objectives were to identify how the reference documents on the online platform define and orientate democratic and participative management; and to discuss the possibilities of autonomy and participation based on public norms concerning democratic management of public schools in Brazil. The methodological approach is qualitative, and documental based on data collected in the referred platform which were treated by content analysis. Our conception of Political Pedagogical Project indicates that it is a procedural and fundamental identity-related school document, directly related to democratic management. We expect this investigation may contribute to academic and social debates related to school management, by helping on building management development actions applicable to schools so that they advance towards the construction of collective and democratic work, and hence, assure the rights of students by pursuing common good through the provision of quality social education.